2014
DOI: 10.1111/ejn.12503
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic neurons in the ventral tegmental area receive dual GABA/enkephalin‐mediated inhibitory inputs from the bed nucleus of the stria terminalis

Abstract: Activation of mu-opioid receptor (MOR) disinhibits dopaminergic neurons in the ventral tegmental area (VTA) through inhibition of γ-aminobutyric acid (GABA)ergic neurons. This mechanism is thought to play a pivotal role in mediating reward behaviors. Here, we characterised VTA-projecting enkephalinergic neurons in the anterior division of the bed nucleus of the stria terminalis (BST) and investigated their targets by examining MOR expression in the VTA. In the BST, neurons expressing preproenkephalin mRNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 67 publications
3
39
0
2
Order By: Relevance
“…Because injection of CRF into the BNST disrupts maternal behavior in lactating females [26], CRF interneurons may also be activated in virgin females presented with pups. Evidence suggests that GABAergic neurons in the BNST would be activated in lactating females presented with pups, because activation of those neurons disinhibits dopaminergic neurons in the VTA [27]. However, pup presentation did not increase the number of c-Fos-positive cells in the BNST of lactating females, even though the number of c-Fospositive cells expressing TH in the VTA increased ( Figs.…”
Section: Discussionmentioning
confidence: 94%
“…Because injection of CRF into the BNST disrupts maternal behavior in lactating females [26], CRF interneurons may also be activated in virgin females presented with pups. Evidence suggests that GABAergic neurons in the BNST would be activated in lactating females presented with pups, because activation of those neurons disinhibits dopaminergic neurons in the VTA [27]. However, pup presentation did not increase the number of c-Fos-positive cells in the BNST of lactating females, even though the number of c-Fospositive cells expressing TH in the VTA increased ( Figs.…”
Section: Discussionmentioning
confidence: 94%
“…The BNST projects inhibitory fibers to the VTA, GABAergic, and GABAergic/enkephalinergic, to modulate response to MOP activation. 140 While behavioral changes are associated with BNST modulation upon chronic morphine administration, AC activity is not affected. 141 While opioid antagonists have been employed experimentally to induce withdrawal in animals treated chronically with opioids, several studies have examined the chronic use of low-dose opioid antagonists to alleviate withdrawal symptoms.…”
Section: Molecular Changes In Other Cns Regionsmentioning
confidence: 99%
“…In addition, a recent study in mice has shown that ENK neurons of the BSTL project to the VTA [Kudo et al, 2014] and may play a role in reward [Jennings et al, 2013b]. These projections are GABAergic and end preferentially on nondopaminergic neurons of the VTA, leading to disinhibition of the dopaminergic neurons [Kudo et al, 2014].…”
Section: The Chicken Dorsal Bstl Includes Pallidal and Striatal Cellsmentioning
confidence: 99%